Dillenia indica L. attenuates diabetic nephropathy via inhibition of advanced glycation end products accumulation in STZ-nicotinamide induced diabetic rats - Navpreet Kaur; Lalit Kishore; Randhir Singh (Journal of Traditional and Complementary Medicine, 2018)
The present study was aimed to evaluate advanced glycation end products (AGEs) inhibitory activity of alcohol and hydro-alcohol extract (DAE and DHE) of Dillenia indica L. (Family: Dilleniaceae) and its potential in treatment of diabetic nephropathy by targeting markers of oxidative stress. D. indica was evaluated for its in vitro inhibitory activity against formation of AGEs by using bovine serum albumin. Diabetes was induced in male Wistar rats by streptozotocin (65 mg/kg i.p.) 15 min after nicotinamide (230 mg/kg, i.p.) administration. Diabetic rats were treated with different doses of extracts (100, 200 and 400 mg/kg) to analyze their nephroprotective effect. Tissue antioxidant enzymes level was measured along with the formation of AGEs in kidney to assess the effect of D. indica in ameliorating oxidative stress. D. indica showed significant inhibition of AGEs formation in vitro. D. indica produced significant attenuation in the glycemic status, renal parameter, lipid profile and level of antioxidant enzymes proving efficacy in diabetic nephropathy. Moreover, D. indica produced significant reduction in the formation of AGEs in kidneys. The present study concludes that D. indica as a possible therapeutic agent against diabetic nephropathy.